A review of the application of active learning pedagogies in undergraduate animal science curricula. (24th January 2023) - Ragland, Elizabeth C; Radcliffe, Scott; Karcher, Elizabeth L
Abstract: With most of the student attrition occurring early in undergraduate educational programs (Braunstein et al., 1997) it is necessary to interest and motivate students early on. The demographics of animal science students have shifted to students with minimal background in food producing animals. This presents a unique challenge as the current student population represents a diverse array of backgrounds and prior experiences. As a result, students enroll in undergraduate animal science programs with various expectations for their undergraduate degree and a focus primarily on careers in veterinary medicine. To engage all students, interest and motivation need to be generated. This review will use motivational frameworks as outlined by the self-determination theory, expectancy value theory, and interest, to explain the impact of the proposed solutions. Active learning classroom strategies are linked to increased knowledge compared with traditional, passive classrooms (Wells et al., 2019). Active learning shifts from a traditional teaching model to a student-centered model, which transitions instructors to facilitators of learning. This review summarizes current proposed pedagogies that have been researched in animal science classrooms such as experiential learning, flipped classrooms, hands-on animal experience, undergraduate research experiences, mentorship opportunities, capstone experiences, service-learning experiences, team-based learning, and cooperative learning. The limitations of these proposed pedagogies and the future research needed are also discussed. Abstract : There are numerous pedagogies that have been implemented in animal science curricula to motivate and spark interest among students. As the student population continues to diversify and grow, it is crucial to understand what literature supports best practices in active learning and future areas of research within animal science teaching programs. Lay Summary: Animal science undergraduate curricula face the issue of motivating and interesting students from diversified backgrounds to meet the growing job market (Benson et al., 2020; Lugar & Stewart, 2019). Students are entering animal science majors with different expectations and values as explained by the expectancy-value theory, so higher education systems face the struggle of meeting diverse student interests while fulfilling required course content. One solution to this challenge is to generate interest and motivation through engaging students in student-centered spaces and creating autonomy, competence and relatedness as outlined by the self-determination theory (Ryan & Deci, 2020). This review examines current research available on different teaching pedagogies in animal science classroom and summarizes their impact. The reviewed pedagogies are possible strategies that institutions can utilize to meet this challenge and motivate students.